2018
DOI: 10.26717/bjstr.2018.07.001554
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining Tissue Architecture in Immediate Implant Placement Following Extraction of Natural Teeth Using Custom Healing Screw

Abstract: The aim of this study was to compare the conventional healing screw with custom healing screw in terms of maintenance of soft tissue architecture. Twenty-four patients who underwent single tooth extraction and single immediate implant placement were included in the study. Twelve patients were treated with conventional healing screw after immediate implant placement (control group) and 12 were treated with screwretained custom healing screw (test group). After minimally traumatic tooth extraction, a temporary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The use of customized healing abutments, when an implant is inserted in a fresh extraction socket, has been described as a beneficial solution that permits to personalize the peri-implant tissues architecture. [15][16][17][18]24,25 This study demonstrated that, in the first month of treatment, the use of customized healing abutments is favorable in preventing linear and volumetric peri-implant tissue loss (Figure 5). CA group exhibited approximately half less the volumetric dimensional variation than CM group (À12.98 ± 14.53 mm 3 and À25.20 ± 17.44 mm 3 ; p = 0.049, respectively).…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…The use of customized healing abutments, when an implant is inserted in a fresh extraction socket, has been described as a beneficial solution that permits to personalize the peri-implant tissues architecture. [15][16][17][18]24,25 This study demonstrated that, in the first month of treatment, the use of customized healing abutments is favorable in preventing linear and volumetric peri-implant tissue loss (Figure 5). CA group exhibited approximately half less the volumetric dimensional variation than CM group (À12.98 ± 14.53 mm 3 and À25.20 ± 17.44 mm 3 ; p = 0.049, respectively).…”
Section: Discussionmentioning
confidence: 82%
“…22,23 On the other hand, the use of customized healing abutments in IIP is a growing subject but almost limited to description of techniques and case reports in terms of scientific evidence. [15][16][17][18]24,25 Recently, an RCT from Perez and colleagues, 26 comparing customized healing abutments and standard healing abutments at IIP sites, showed favorable results in terms of papilla presence and marginal bone loss at the sites treated with customized abutments, when compared with the standard healing abutments sites. In our investigation, all the experimental sites were carefully selected and classified as type 1 extraction sockets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To cope with this anatomical consideration several authors have proposed using a customized abutment to seal the large molar socket after the immediate implant placement, and maintaining the original outline of soft tissues 21‐26 . For instance, the Sealing Socket Abutment (SSA) technique introduced by Finelle et al 2017 uses an individualized chairside‐fabricated abutment following tooth extraction to seal the surgical area and to protect the bone grafting material from the oral cavity exposure as well.…”
Section: Introductionmentioning
confidence: 99%